USAHA TANI KOPI ROBUSTA DI KABUPATEN TANGGAMUS: KAJIAN STRATEGI PENGEMBANGAN AGROBISNIS - Widya Ariyanti; Any Suryantini; jamhari jamhari (Jurnal Kawistara, 2019)
Robusta coffee in the Regency of Tanggamus has enormous development prospects in the field of farming and agroindustry as it has the potential to generate regional income. In order to realise this potential a single encompassing strategy is needed to achieve a final outcome that is more efficient and effective. The aim of this research is to (1) Knowing the strengths and weaknesses, opportunities and threats of robusta coffee farming and agroindustry(2) formulate strategy for robusta coffeefarming and agroindustry development in Tanggamus Regency. This research was conducted on coffee farmers and ground coffee processing in Tanggamus Regency. The sampling technique of coffee farmers use a simple random sampling method of 68 coffee farmers. The data is obtained from primary data and secondary data. Techniques of data gathering are structured interviews using questionnaires and direct observation. Farm analysis are used SWOT is used to determine the strategy. The strategy for developing robusta coffee in Tanggamus Regency is to minimizing weaknesses to achive  potential opportunities by: land extension, planting qualified seed and replanting unproductive coffee trees, diffusion of red bean harvesting technology, increasing ground coffee production capacity and procurement of machinery,complete legal registration number on the packaging and promotion of ground coffee.